Production of a bovine IL-12p40 probe and application using in situ hybridization on ruminant fixed tissues - Canton, German Jose; Bartley, Paul M.; Bartley, Kathryn; Todd, Helen; Chianini, Francesca; Katzer, Frank (Elsevier, 2019)
Pro-inflammatory cytokines (particularly IL-12) are important for initiating protective T helper 1 (Th1)-type immune responses and hence vital for combating intracellular infections and tumours. In situ hybridization (ISH) provides a powerful diagnostic tool allowing the identification and localization of cells producing these mediators in fixed tissues. The objective of this work was to produce a bovine IL-12p40 probe that allows detection of IL-12p40 mRNA in fixed tissues from different ruminant species. The RNA probe sequence is 447 bp in length and from a region with high cross-species-sequence homology (>97.3% homology) to the ovine, cervine, caprine and bubaline IL-12p40 genes. ISH was carried out on paraformaldehyde fixed tissues collected from cattle, sheep and goats. The probe was efficient in identifying IL-12p40 expressing cells in fixed tissues from all these species. In conclusion, the IL-12p40 probe was efficient in identifying and localizing cells that express IL-12p40, and provides a good immuno-diagnostic technique to characterize immune responses in fixed tissues.